Pengujian Daya Hasil Beberapa Varietas Tanaman Jagung pada Kondisi Cekaman Kekeringan yang Diberi Pupuk Kandang di Lahan Kering Lombok Utara - IGM Kusnarta; I Wayan Sudika (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2018)
This study aimed to determine the efficacy of several varieties of maize at various rate of manure under drought condition on the dry land of North Lombok. The experiments were designed using split plot design, with manure rates (0, 5, 10, 15 and 20 t.ha-1) as the main plots, and five different maize varieties (P4IS, Gumarang, Lamuru, Sukmaraga and NK212 Hybrid) as subplots. The efficacy of several maize varieties were determined from the weight of dry seeds per plant. Experimental data were analyzed using analysis of variance (ANOVA) at 5 percent significant levels. The mean of each treatments was further tested using the Honestly Significant Difference (HSD) at the same level. The results showed that the highest yield of maize crop was obtained on Lamuru variety at rate of manure of 20 t/ha, ie 85.94 g.plant-1 or 6.14 t.ha-1. The yield of Lamuru variety is similar to that of Sukmaraga, but it is higher compared to P4IS, Gumarang and Hybrid of NK212.The highest yield of maize crop was obtained at rate of manureof 20t.ha-1.